THE USE OF LIVEWORKSHEETS AND PROBLEM BASED LEARNING (PBL) MODELS IN IMPROVING STUDENTS' CRITICAL MATHEMATICAL THINKING SKILLS - Siti Lisa Bitasmi’ah; Isnarto; Nuriana Rachmani Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Mathematics is one of the subjects given to students starting from elementary school to college. Mathematics learning aims to develop students in thinking logically, analytically, regularly and critically. Problem Based Learning (PBL) is a teaching method that presents real-world situations in the learning process with the aim of improving students' critical thinking skills in interactive learning. Interactive learning using Liveworksheets allows teachers to present material in a more interesting and challenging way, so that students are more actively involved in the learning process. This study aims to determine: (1) the effectiveness of using Liveworksheets in improving students' mathematical critical thinking skills, (2) the effectiveness of the Problem Based Learning (PBL) learning model in improving students' mathematical critical thinking skills. The preparation of this article uses the SLR (Systematic Literature Review) method where the articles collected are only articles published within a maximum of the last 6 years (2019-2025). Based on the results of this study, it was found that the use of Liveworksheets in the Problem Based Learning (PBL) learning model can improve students' mathematical critical thinking skills.